In vitro multiplication and somatic embryogenesis of Perezia pinnatifida (Asteraceae) medicinal Andean plant - Olivera-Gonzales, Percy (2017)
This work inform on in vitro propagation of the "valeriana" Perezia pinnatifida (Humb. & Bonpl.) Wedd. Shoot multiplication and indirect somatic embryogenesis methodologies were performed. The basal culture medium for all stages was Murashige and Skoog, middle of salts supplemented with 2.0% sucrose, 0.3% phytagel and pH 5.67; the treatments were prepared with or without phytohormones. The hormonal supplements for the shoot multiplication were: BAP 1.0 mg.L-1 + ANA 0.01 mg.L-1, and BAP 1.0 mg.L-1; for embryogenic callus induction were: ANA or 2,4-D (1.0 mg.L-1 and 2.0 mg.L-1); and for the embryo germination were: BAP (0.5 and 1.0 mg.L-1) or BAP 0.5mg.L-1 + ANA 0.05mg.L-1. BAP 1.0 mg.L-1 produced the higher number buds. For somatic embryogenesis, ANA 1.0 mg.L-1 induced a greater area of embryogenic callus, and BAP 0.5 mg.L-1 allowed major germination of the somatic embryos.